2015
DOI: 10.14202/vetworld.2015.1370-1374
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of molecular and microscopic technique for detection of Theileria annulata from the field cases of cattle

Abstract: Aim:Tropical theileriosis is fatal hemoprotozoal disease of dairy animals caused by Theileria annulata. The aim of the present study was to detect the T. annulata and comparison of results of molecular and microscopic techniques.Materials and Methods:A total of 52 blood samples were collected from the cattle suspected for theileriosis across the Banaskantha district. All the samples were screened for theileriosis using Giemsa’s staining technique and polymerase chain reaction (PCR).Results:Total of 17 (32.69%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 14 publications
3
8
0
Order By: Relevance
“…This is due to the unavailability of molecular and serological diagnostics and resource limitations in most rural veterinary hospitals and clinical settings [ 49 ]. The relative sensitivity and specificity of the blood microscopy, as a diagnostic technique, validated previous findings [ 38 , 45 ]. However, the presence of artifacts, the destruction of the piroplasmic form due to hemolysis (RBCs), thick smear formation, improper staining, lack of microscopic expertise, and low parasitemia, are all the factors that diminish its sensitivity [ 37 , 50 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This is due to the unavailability of molecular and serological diagnostics and resource limitations in most rural veterinary hospitals and clinical settings [ 49 ]. The relative sensitivity and specificity of the blood microscopy, as a diagnostic technique, validated previous findings [ 38 , 45 ]. However, the presence of artifacts, the destruction of the piroplasmic form due to hemolysis (RBCs), thick smear formation, improper staining, lack of microscopic expertise, and low parasitemia, are all the factors that diminish its sensitivity [ 37 , 50 ].…”
Section: Discussionsupporting
confidence: 84%
“…Acaricides application was also evaluated as potential risk factor that influence TT prevalence in the cattle population (univariate: P<0.05, OR: 3.4, 95% CI: 2.5–4.6; multivariate: P<0.05, OR: 1.4, 95% CI: 0.9–2.0). Acaricides application as a potential risk factor for TT agreed with the assessment of the published literature from other agro-ecological zones of the country, which presented that regular and proper acaricidal application on cattle could control tick vector and ultimately TT incidence in the endemic region [ 2 , 20 , 45 ].…”
Section: Discussionsupporting
confidence: 66%
“…These differences were explored in more detail using statistical approaches (see below). The results support previous studies demonstrating diagnosis of carrier animals is significantly more sensitive by PCR assay relative to blood smear [15,16]. All samples that scored as positive for Theileria spp.…”
Section: Prevalence Of Infection and Sensitivity Of Diagnostic Technisupporting
confidence: 89%
“…Similar to the current results, Hoghooghi-Rad et al (2011) found that the semi-nested PCR accurately revealed 12 (7.5%) positive bovine blood specimens in Golestan province of Iran. In Banaskantha district, India, Chauhan et al (2015) recorded that 24 (46.15%) cows were infected with T. annulata using Tams1 gene-based PCR. Concomitantly, Acharya et al (2017) recovered 68% (34/50) infection rate of theileriosis in cattle in Odisha, India using PCR.…”
Section: Discussionmentioning
confidence: 99%